Sensibility Test of Candida species against Nystatin, Ketoconazole, and Fluconazole on Oral Candidiasis with HIV/AIDS using Disc Diffusion Method - Cut Shelma Maharani; Rahmadewi Rahmadewi; Afif Nurul Hidayati; Dwi Murtiastutik (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Oral candidiasis is one of the most common infections in Human Immunodeficiency Virus/Acquired Immuno Deficiency Syndrome (HIV/AIDS) patients. Some studies have reported an increased number of resistances of Candida sp. against several antifungal therapies. Purpose: To evaluate the pattern of Candida sp. causing oral candidiasis and the pattern of resistance among the Candida sp. against nystatin, ketoconazole, and fluconazole in oral candidiasis patients with HIV/AIDS infection. Methods: This was a descriptive observational study conducted at the Infectious Disease Intermediate Care Unit (UPIPI) Dr. Soetomo General Academic Teaching Hospital. Candida sp. was identified using conventional methods, while the sensibility test was done by using disc diffusion methods. Result: There were 26 subjects with 50 isolates of Candida sp. that had been cultured successfully. Non-albicans Candida sp. was the most common species, which was observed in 28 subjects (56%). The results of the sensibility test on Candida sp. against nystatin, ketoconazole, and fluconazole were 0 (0%), 3(6%), dan 23(46%) respectively. Conclusion: The increased resistance among Candida sp. against antifungal drugs, especially fluconazole, could raise awareness in drug prescription, especially for HIV/AIDS patients.